Visual & Linguistic elements of Palestinian cartoon : How can this be applead in language teaching - Gilang Lailatul Megadini; Fera Zasrianita; Andriadi Andriadi (Journal of Innovative and Creativity, 2025)
This qualitative study investigates how Multimodal Critical Discourse Analysis (MCDA) can be applied to explore the sociopolitical messages embedded in Palestinian cartoons. Focusing on symbolic imagery, emotional language, and rhetorical strategies, the research examines how these multimodal elements shape meaning and influence audience interpretation. Data were collected through classroom observations and in depth interviews with fourth semester English Education students at UIN Fatmawati Bengkulu. Findings show that the integration of visual and textual elements in Palestinian cartoons fosters empathy, critical reflection, and social awareness of humanitarian and political issues. Students demonstrated greater awareness of how multimodal features reinforce ideological messages, enabling them to interpret contextual meanings and express informed perspectives. Although some initially found it challenging to decode layered symbolism, targeted scaffolding supported their interpretive skills. Overall, the study highlights Palestinian cartoons as effective pedagogical tools for enhancing critical thinking, contextual analysis, and engagement with real-world discourse in language learning.